Assessment of insecticide poisoning among vector control operators using a new biomarker, the enyzme β-glucuronidase - Rostam, Muhamad Ashraf; Hassan, Zuridah (University Publication Centre (UPENA) UiTM, 2011)
The increase of insecticide space spraying to control Aedes mosquitoes submits vector control operators to low-level exposure to toxic organophosphates. Plasma β-glucuronidase level is found to increase in most organophosphate poisoning cases. This study aims to identify presence of organophosphate poisoning using β-glucuronidase assay as an alternative biomarker. A total of 180 blood samples (74 controls and 106 subjects) were examined for this enzyme using a spectrophotometer. These results were then compared to the routine screening assay, butyrylcholinesterase (BChE) assay using a chemical analyzer. Both results showed absence of organophosphate poisoning indicated by no increased in β-glucuronidase level with no reduced in BChE level. Results of BChE level in the subject group (7879.70 ±227.935 IU/L), was significantly higher than the control group (7067.86 ±1609.712 IU/L) (p<0.05). Meanwhile, β- glucuronidase level between the subject (194.48 ±114.711 U/dL) and control group (192.60 ±122.685 U/dL) showed no significant difference (p>0.05). The findings of this evaluation show that assaying for the β-glucuronidase enzyme can be an alternative method to determine organophosphate poisoning. Furthermore, β-glucuronidase assay using spectrophotometer is recommended due to its ease of use and suitability for small laboratories with limited facilities.